LYMPHATIC FILARIASIS: AN OVERVIEW - KANAAN AL-TAMEEMI; RAIAAN KABAKLI (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Lymphatic filariasis (LF) is a tropical disease caused by infection with the parasitic filarial worms: Wuchereria bancrofti, Brugia malayi, and Brugia timori. The symptoms of this chronic disease appear in adults (in men more than in women) and include damage to the lymphatic system, arms, legs, and genitals, which cause significant pain, reducing productivity, and social problems. LF is a cause of continued disability, pain, disfigurement, and sexual disability in the world, so the knowledge of the disease and the infection control is very important. In addition to the importance of prevention, that includes giving medicine and using controlling ways of mosquitoes. Moreover, the prevention of disease is important, that includes giving medicine and using controlling ways of mosquitoes. However, although the efforts of health organizations to reduce the LF infections, there are still many challenges including the early diagnosis and control of infection among people.